2004
DOI: 10.21930/rcta.vol5_num1_art:25
|View full text |Cite
|
Sign up to set email alerts
|

Calidad nutritiva de las arbustivas forrajeras Malvaviscus arboreus, Codariocalyx gyroides y Cratylia argentea en la zona de ladera de los Departamentos de Cauca y Valle, Colombia

Abstract: <p>Después de evaluar la adaptación de 25 especies arbustivas en fincas ubicadas en zonas de ladera del trópico medio de los departamentos de Cauca y Valle del Cauca, se realizó el estudio de consumo y caracterización bromatológica e las tres especies con mayor potencialidad en sistemas productivos mixtos (ganadería doble propósito-agricultura): <em>Malvaviscus arboreus</em>, <em>Cratylia argentea </em>y <em>Codariocalyx gyroides</em>. La evaluación de calidad y consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
1
Order By: Relevance
“…In the current study, mean ASH and organic matter (OM) contents were found to be within satisfactory limits (Table 1). The ASH results for C. argentea (8.30%) and P. discolor (7.60%) are lower than those reported in previous studies by Celis et al, (2004) and Riascos et al, (2020) respectively. The variation in the results may be influenced by characteristics such as habitat and soil conditions where sampling was conducted (Hussain & Durrani, 2009).…”
Section: Resultscontrasting
confidence: 69%
“…In the current study, mean ASH and organic matter (OM) contents were found to be within satisfactory limits (Table 1). The ASH results for C. argentea (8.30%) and P. discolor (7.60%) are lower than those reported in previous studies by Celis et al, (2004) and Riascos et al, (2020) respectively. The variation in the results may be influenced by characteristics such as habitat and soil conditions where sampling was conducted (Hussain & Durrani, 2009).…”
Section: Resultscontrasting
confidence: 69%